PERANAN KEPOLISIAN RESOR BUKITTINGGI DALAM PENANGGULANGAN TINDAK PIDANA PENCABULAN TERHADAP ANAK - Jefri, Jefrizal (LPPM Universitas Ekasakti Padang, 2018)
Passage 81 and 82 of Law Number 35 Year 2014 about The Changing of the Law Number 23 Year 2002 regulate about sanction to the agent of violence. The Law underlines to give effect and push the concrete steps in maintenance physic, psychic, and social of children. The violence is bad action. Children often become victims of this violence.The problems in this study are: First, how is the role of Bukittinggi Resort Police in crime prevention to children? Second, what are the obstacles faced by Bukittinggi Resort Police in crime prevention to children and how to solve it? The specification of this research is descriptive analytic. The method uses in this research is the normative and juridical empiric method. The techniques of collecting data uses are field study by interviewing for the primary data and library study for the secondary data. Then, the data analyzed qualitatively in descriptive analysis form. From the research results obtained several conclusions: First, role of Bukittinggi Resort Police in crime prevention to children done through preventive and repressive efforts. The preventive through socialization to pupils, parents and schools.Therefore, the repressive efforts by prohibition effort and investigation.The prohibition of crime prevention to children by socialite.The efforts of investigation suitable by police such as investigation, etc. Second, the obstacles faced by Bukittinggi Resort Police in crime prevention to children is lack of enthusiasm children, societies and teachers and development of technology and information. Others, the obstacles in investigation are unwished of victim to report, difficult to evidence, there are so many requirements should be done and limitation of investigation fund. The efforts to solve the problems are socialite, increase investigation, socialite regulation of ITE, coordination of many sides and increasing of fund.